2005
DOI: 10.1139/x05-110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in landscape composition and stand structure from 1945–2002 on an industrial forest in New Brunswick, Canada

Abstract: Detailed 1944–1947 cruise data and maps were used to compare species composition, age-class distribution, and stand structure between 1945 and 2002, for a 190 000 ha industrial forest in New Brunswick, Canada. Softwood forest area in 1945 and 2002 was similar, at 40% and 42%, respectively, but mixed hardwood–softwood decreased from 37% to 18%, and hardwood increased from 10% to 25%. Forest management from 1945 to 2002 resulted in the forest (1) becoming younger, with 86% of the trees >70 years old in 2002 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 31 publications
0
41
2
1
Order By: Relevance
“…2) originated primarily from logging activities, severe defoliation and tree mortality caused by the last spruce budworm outbreak (1970-1987Morin et al 1993) generated some regeneration areas in 1983 and 1994 (Kneeshaw and Bergeron 1998). Working in a similar mixed-forest landscape in New Brunswick, Etheridge et al (2005) found that stand successional dynamics were highly variable between 1945 and 2002 as a result of the mixed effects of harvesting, plantations, and spruce budworm outbreaks. The increase in area of Cohort 1 patches between 1965 and 1983 in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2) originated primarily from logging activities, severe defoliation and tree mortality caused by the last spruce budworm outbreak (1970-1987Morin et al 1993) generated some regeneration areas in 1983 and 1994 (Kneeshaw and Bergeron 1998). Working in a similar mixed-forest landscape in New Brunswick, Etheridge et al (2005) found that stand successional dynamics were highly variable between 1945 and 2002 as a result of the mixed effects of harvesting, plantations, and spruce budworm outbreaks. The increase in area of Cohort 1 patches between 1965 and 1983 in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). This area belongs to the Southern Upland ecoregion and comprises 190,000 ha of mostly conifer forests that today ranks as one of the most intensively managed parts of Canada (Etheridge et al 2005). Elevation ranges from 180 to 600 m (NBDNRE 1998) although no stands included in this study were located above 400 m. Young forests regenerating after wildfire were sampled in three areas that experienced intense crown-fires during 1972-1976 (area 2 in Fig.…”
Section: Study Areamentioning
confidence: 99%
“…The lack of sensitivity of softwood growing stock to increased area of reserves resulted from the make-up of this landbase, as: 1) much of the area added as reserves was in mixedwood or hardwood ecosites (Table 2); and 2) most future softwood timber supply was coming from plantations (39-64% of the landbase in various scenarios), which provided the majority (82%) of the softwood growing stock. In 2002, natural softwood made up only 6% of the District, 4% of which was in riparian buffers (Etheridge et al 2006); the landbase included roughly 25 000 ha softwood-cedar, 79 000 ha softwood (only 1140 ha of natural stands > 50 years old), 32 000 ha mixedwood, and 46 000 ha hardwood (Etheridge et al 2005). Model constraints (Table 4) mandated the maintenance of 12 000 ha of softwood (9500 ha of old cedar, 1000 ha of black spruce, and 1500 ha of balsam fir), as well as at least 9000 ha of mixedwood and 40 000 ha of hardwood.…”
Section: Softwood and Hardwood Growing Stockmentioning
confidence: 99%
“…In period 16, there were 2600 ha of old mixedwood with no reserves versus 4600 ha with 15% reserves. Old mixedwood was the most constraining habitat, is limiting for some wildlife in the District (Higdon et al 2005), and has decreased from 28% of the landbase in 1945 to 18% in 2002 (Etheridge et al 2005). Fig.…”
Section: Projected Deer Wintering Area and Old Habitatmentioning
confidence: 99%